The French book and the European book world - Pettegree, Andrew (Library of the written word, 2007)
France, in the sixteenth century, was one of the great centres of the European publishing industry. This book offers a series of linked studies of European print culture of the sixteenth century, focusing particularly on France and the regional, provincial experience of print.